2021
DOI: 10.3390/ijms22179474
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Intestinal Microbiota Dysbiosis Impairs Mucosal Homeostasis by Modulating Toll-like Receptor Signaling Pathways

Abstract: Chemotherapy-induced intestinal mucositis, a painful debilitating condition affecting up to 40–100% of patients undergoing chemotherapy, can reduce the patients’ quality of life, add health care costs and even postpone cancer treatment. In recent years, the relationships between intestinal microbiota dysbiosis and mucositis have drawn much attention in mucositis research. Chemotherapy can shape intestinal microbiota, which, in turn, can aggravate the mucositis through toll-like receptor (TLR) signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 109 publications
0
31
0
1
Order By: Relevance
“…It is worth noting that the majority of patients in our study (42/49) received chemotherapy concurrent with radiotherapy. Previous studies found that chemotherapy-induced gut microbiota dysbiosis can impair mucosal homeostasis ( van Vliet et al, 2010 ; Wei et al, 2021 ). However, we found no significant difference in the alpha diversity indexes (Shannon and Chao1) of gut microbiota in the mid-treatment samples of patients who received chemoradiotherapy relative to those who received radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the majority of patients in our study (42/49) received chemotherapy concurrent with radiotherapy. Previous studies found that chemotherapy-induced gut microbiota dysbiosis can impair mucosal homeostasis ( van Vliet et al, 2010 ; Wei et al, 2021 ). However, we found no significant difference in the alpha diversity indexes (Shannon and Chao1) of gut microbiota in the mid-treatment samples of patients who received chemoradiotherapy relative to those who received radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hb. Dendrobii can modulate macrophage activity via the NF-kB pathway and has been shown to act as an immune modulator to regulate gastrointestinal mucosal barrier function [ 26 , 27 ]. Rx.…”
Section: Discussionmentioning
confidence: 99%
“…Not unlike E. coli, Clostridium perfringens interact with occludin to result in its redistribution and removal from the TJs [85]. Chemotherapy also decreases the microbial diversity of the intestinal microbiota [86,87], including producers of SCFAs like butyrate. Butyrate, in particular, is not only needed for enterocyte health and TJ development but also has strong anti-inflammatory effects that reduce intestinal injury and maintain the mucus layer [88][89][90][91].…”
Section: Chemotherapy-induced Disruption Of the Intestinal Barriermentioning
confidence: 99%